Effect of the combination of automated peripheral mechanical stimulation and physical exercise on aerobic functional capacity and cardiac autonomic control in patients with Parkinson’s disease: a randomized clinical trial protocol - Zelada-Astudillo, Nicolle; Moreno, Vinicius Christianini [UNESP]; Herrera-Santelices, Andrea; Barbieri, Fabio Augusto [UNESP]; Zamunér, Antonio Roberto (Springer Nature, 2021)
Background: Automated peripheral mechanical stimulation (AMPS) has been proposed as a new complementary therapy with potential for improving motor and cardiovascular abnormalities in Parkinson’s disease (PD). However, AMPS long-term effects and its combination with physical exercise are unknown. Thus, this study aims to compare the effects of a program of 12 weeks of physical exercise with a 12-week intervention program combining physical exercise and AMPS on the aerobic capacity, cardiac autonomic control, and gait parameters in patients with PD. Methods: A randomized, controlled clinical trial will be conducted. Older volunteers with PD will be randomly assigned to one of the two groups studied: (1) exercise or (2) AMPS + exercise. Both groups will undergo an exercise program of 24 sessions, for 12 weeks, performed twice a week. Before exercise sessions, the group AMPS + exercise will receive a session of active AMPS, while the group exercise will receive an AMPS sham intervention. Shapiro-Wilk’s and Levene’s tests will be used to check for data normality and homogeneity, respectively. In case parametric assumptions are fulfilled, per-protocol and intention-to-treat analyses will be performed using a mixed model analysis of variance to check for group*time interaction. Significance level will be set at 5%. Discussion: Several non-pharmacological treatment modalities have been proposed for PD, focusing primarily on the reduction of motor and musculoskeletal disorders. Regular exercise and motor training have been shown to be effective in improving quality of life. However, treatment options in general remain limited given the high prevalence and adverse impact of these disorders. So, developing new strategies that can potentiate the improvement of motor disabilities and also improve non-motor symptoms in PD is relevant. It is expected that the participants from both groups will improve their quality of life, gait parameters, and their cardiac autonomic control, with greater improvements being observed in the group combining active AMPS and physical exercise. Trial registration: ClinicalTrials.gov NCT04251728. Registered on February 05, 2020.
Keywords: Aged; Exercise; Parkinson’s disease; Randomized controlled trial; Rehabilitations